(untitled) (INNOVATIVE ECONOMY, 2020)
Pruntseva G.О. THE DEVELOPMENT OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF FOOD SECURITY IN ANCIENT TIMES Purpose. The aim of the study is to determine the basic principles of food security in ancient times and highlight the first tools of food security mechanism, which allowed for the further development of society. Methodology of research. The following methods are used in the research process, namely: analytical and historical methods to analyze the historical development of the main tools for ensuring food security. Assessment and logic are used to formulate the conclusions of the historical analysis. Findings. It is found that the problem of food security was relevant in primitive times. In ancient times, the following tools can be distinguished: warehousing and distribution of food products among all members of the community. The main characteristics of the organizational and economic mechanism of food security in ancient times are determined. The historical development of the food supply system of the population is analyzed. Originality. The main components of the food security system in ancient times are highlighted. For the first time the main tools of the food system are identified. It is proved that with the advent of the first states and the development of irrigation facilities, agricultural production became more efficient, namely: the use of agricultural technologies made it easier for people to work and increased agricultural production productivity. The development of transport infrastructure ensured the efficient exchange and trade of food products. Practical value. The author’s generalizations regarding the use of food security tools by primitive and ancient civilizations are important in the modern system of economic relations since, in the absence of effective medical treatment and government support for the vulnerable groups of the population, they ensured the survival of primitive people and the development of ancient civilizations. The results of the study are the basis for improving the modern mechanism of food security and will help to formulate an effective state policy in the field of food security. Key words: food security; agricultural production; prices; products; exchange; social programs.